1443. Serotypes 8 and 3 Are the Leading Cause of Invasive Pneumococcal Disease in Adults in Portugal (2015–2017). (26th November 2018) - Silva-Costa, Catarina; Lopes, Elísia; Ramirez, Mario; Melo-Cristino, Jose; ,
Abstract: Background: In Portugal, following the use of PCVs in children, there were major changes in the serotype distribution of the pneumococcal population in adult pneumococcal invasive disease (IPD). The inclusion of PCV13 in the National Immunization Plan in 2015 could have an even greater impact on adult IPD. To evaluate this, we monitored the serotypes and antimicrobial resistance of invasive pneumococcal isolates in 2015–2017. Methods: A total of 1, 495 adult IPD isolates were recovered, serotyped by Quellung and tested for susceptibility to antimicrobials by disk diffusion or Etest. Results: The number of isolates recovered in each year remained approximately constant. Among the 1, 495 isolates, 58 different serotypes were found and only a small proportion of these were nontypeable (0.6%, n = 9). The most common were serotypes 8 (18%), 3 (15%), 22F and 14 (7% each), 19A (6%), and 20 (4%). The majority of isolates expressed serotypes exclusively found in the 23-valent polysaccharide vaccine (41%, n = 619). A considerable number of isolates expressed PCV serotypes ( n = 563), of which 207 isolates (14%) expressed PCV7 serotypes and the remaining isolates expressed the additional serotypes included in PCV13 ( n = 356, 24%). Non-vaccine types (NVT) were found in 313 isolates ( n = 21%) and among these, serotypes 6C, 15A, 16F, 23A and 31 were the most prevalent, together accounting for approximately half of the NVT. Overall, 19% of the isolates presented resistance to erythromycin and penicillin nonsusceptibility was found in 17% of the isolates recovered in 2015–2017. Conclusion: After several years of pneumococcal conjugate vaccines use in children, PCV serotypes are still frequently responsible for adult IPD. Moreover, serotypes exclusively found in PPV23 were also found to be important causes of invasive disease in this period, suggesting an important role for vaccination in disease prevention in this age group. Disclosures: M. Ramirez, Pfizer: Speaker's Bureau, Speaker honorarium; GlaxoSmithKline: Consultant, Consulting fee; Merck Sharp and Dohme: Consultant, Consulting fee. J. Melo-Cristino, Pfizer: Grant Investigator and Speaker's Bureau, Research grant and Speaker honorarium; Merck Sharp and Dohme.: Speaker's Bureau, Speaker honorarium.